Disease-free survival in patients with non-metastatic breast cancer - Diniz,Roberta Wolp (2016)
SUMMARY Introduction: Breast cancer is the second most common malignancy in the world and the one with highest incidence in the female population; it is also a major cause of death from cancer among women. Objective: To analyze the disease-free survival (DFS) at 5 years and prognostic factors in women with non-metastatic invasive breast cancer treated at a referral center for cancer care located in a medium-sized city in the Southeast of Brazil. Method: Patients diagnosed with the disease between 2003 and 2005 and identified through the institution’s cancer hospital records were analyzed. The follow-up of cases was carried out through hospital records, and complemented by search in the database of the Mortality Information System (SIM) as well as telephone contact. The variables analyzed were distributed in the following blocks: socio-demographic data, tumor-related characteristics, and treatment-related characteristics. Survival functions were calculated using the Kaplan-Meier method and the prognostic factors were analyzed based on Cox proportional hazard model. Results: The study showed a DFS at 5 years of 72% (95CI 67.6-75.9). The main variables independently associated with DFS were lymph node involvement, use of hormone therapy, and education level. Conclusion: This study reinforces the importance of early diagnosis for DFS, pointing to the role of social aspects in this regard. The relevance of this research in the country is also highlighted, given the scarcity of studies on DFS in the Brazilian population.